Growth of SrWO₄ and CaMoO₄ single crystals and their characterization by means of Raman spectroscopy - Kosmyna, M.B.; Shekhovtsov, A.N.; Khodasevich, I.A.; Voitikov, S.V.; Orlovich, V.A. (Functional Materials, 2017)
The SrWO₄ and CaMoO₄ crystals grown under different conditions by the Czochralski method were studied by means of Raman spectroscopy. Raman spectra of the crystals were measured and peaks were identified. For SrWO₄ crystals 2nd and 3rd Stokes were observed for the first time.